Improving Predictions of Climate Change–Land Use Change Interactions - Schulte to Bühne, Henrike; Tobias, Joseph A.; Durant, Sarah M.; Pettorelli, Nathalie (Trends in ecology & evolution (Amsterdam), 2021)
Climate change and land use change often interact, altering biodiversity in unexpected ways. Research into climate change–land use change (CC–LUC) interactions has so far focused on quantifying biodiversity outcomes, rather than identifying the underlying ecological mechanisms, making it difficult to predict interactions and design appropriate conservation responses. We propose a risk-based framework to further our understanding of CC–LUC interactions. By identifying the factors driving the exposure and vulnerability of biodiversity to land use change, and then examining how these factors are altered by climate change (or vice versa), this framework will allow the effects of different interaction mechanisms to be compared across geographic and ecological contexts, supporting efforts to reduce biodiversity loss from interacting stressors. Climate change–land use change (CC–LUC) interactions have a wide range of effects on biodiversity.Current research focuses on classifying interaction types by identifying unexpected biodiversity outcomes under combined climate change and land use change.The mechanisms underpinning these interactions are often overlooked, limiting our ability to predict biodiversity change and inform conservation responses.The concept of risk focuses attention on how climate change alters the exposure, sensitivity, and adaptive capacity of biodiversity in the face of land use change (and vice versa).Risk frameworks can improve our understanding of CC–LUC interaction mechanisms, offering a method for identifying species and ecosystems at risk from these interactions, as well as for targeting conservation responses.